Assessment of Time Management Scale of Science, Technology and Engineering Learners - Dominado, Noel L.; Pangan, Lyskee Jane G.; De Guzman, Georgina Paula P.; Pineda, Ritchie O.; Navarro, Jolo L.; Lopez, Rheyneil Jairuz B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study aims to assess the time management strategies of Science, Technology, and Engineering (STE) students in one of the public secondary high schools in Cluster 1 Division of Pampanga, Philippines. It aims to understand their challenges, techniques, and the role of technology in their daily academic routines. Effective time management is important for balancing schoolwork, extracurricular activities, and personal responsibilities, yet many students struggle with prioritization and planning. A sequential explanatory approach is employed, combining quantitative and qualitative data. The study first collected responses from a standardized questionnaire to evaluate students' time management habits. Qualitative interviews with selected participants followed this to gain deeper insights into their experiences. The results showed that some students have good habits, like learning from mistakes, while many rely too much on their phones to keep track of time instead of using planners or calendars. Technology also causes distractions, leading to procrastination and stress. Students often struggled with last-minute cramming and lack of sleep. To improve time management, students should plan their tasks, break significant assignments into smaller steps, and limit their time on non-school-related apps. This study showed that better time management could help students feel less stressed and perform better in school.